Greenpeace: Sebuah Gerakan Sosial Dan Politik Hijau Di Indonesia (Kampanye Greenpeace Di Jakarta 2006-2021 - Luthfi Ridzki Fakhrian; Abrar Abrar; Firdaus Hadi Santosa (Departement of Mathematics Education, 2024)
This research aims to reconstruct the Green Social and Political Movement implemented by Greenpeace from 2006 to 2021 through campaign methods. This research uses a historical approach designed in a descriptive-analytical format, based on critical analysis that follows the principles suggested in historical research. The historical method is a critical process of examining and analyzing records and remnants of the past, to show how influential Greenpeace's green social and political movements are through campaign strategies and providing solutions and recommendations in pressuring the government in Jakarta. Provide a deeper understanding of Greenpeace's efforts in responding to environmental challenges in Jakarta so that they can conduct